1991
DOI: 10.1111/j.1471-4159.1991.tb01990.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Histamine Release from the Rat Hypothalamus as Measured by In Vivo Microdialysis

Abstract: The release of endogenous histamine (HA) from the hypothalamus of anesthetized rats was measured by in vivo microdialysis coupled with HPLC with fluorescence detection. Freshly prepared Ringer's solution was perfused at a rate of 1 microliter/min immediately after insertion of a dialysis probe into the medial hypothalamus, and brain perfusates were collected every 30 min into microtubes containing 0.2 M perchloric acid. The basal HA output was almost constant between 30 min and 7 h after the start of perfusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
46
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(52 citation statements)
references
References 38 publications
6
46
0
Order By: Relevance
“…This original finding is interesting from the point of view that it has previously been demonstrated that the PVN plays a central role in the histaminergic regulation of food intake 21 and that it harbours a population of H 1 and H 3 receptors. 22 This finding adds further support to the view that the histamine H 3 receptor is essential for regulating the histamine release and synaptic histamine concentration, 15,16,[23][24][25] and that this concentration can be increased Neural histamine and food intake K Malmlöf et al as thioperamide 26,27 are associated with an acute decrease of food intake. In one study performed by Attoube et al, 28 these findings were reproduced also after peripheral administration of the same drug.…”
Section: Discussionsupporting
confidence: 54%
“…This original finding is interesting from the point of view that it has previously been demonstrated that the PVN plays a central role in the histaminergic regulation of food intake 21 and that it harbours a population of H 1 and H 3 receptors. 22 This finding adds further support to the view that the histamine H 3 receptor is essential for regulating the histamine release and synaptic histamine concentration, 15,16,[23][24][25] and that this concentration can be increased Neural histamine and food intake K Malmlöf et al as thioperamide 26,27 are associated with an acute decrease of food intake. In one study performed by Attoube et al, 28 these findings were reproduced also after peripheral administration of the same drug.…”
Section: Discussionsupporting
confidence: 54%
“…The initial characterization of H 3 autoreceptors used histamine release from brain slices, and the first report of H 3 antagonist-evoked histamine release in the whole animal was demonstrated in the hypothalamus of thioperamidetreated rats (Itoh et al, 1991;Mochizuki et al, 1991 receptor antagonism produced by systemic administration of 5-cyclohexyl-1-(4-imidazol-4-ylpiperidyl)pentan-1-one (GT-2016) increased histamine in the parietal cortex of awake, freely moving rats (Tedford et al, 1995). In addition, several selective H 3 antagonist have been shown to increase extracellular histamine levels in the rat prefrontal cortex, the TMN, and the basolateral amygdala after systemic thioperamide administration (Cenni et al, 2004).…”
Section: H 3 Receptor Modulation Of Neurotransmitter Releasementioning
confidence: 99%
“…In contrast, presynaptic H 3 receptors are almost exclusively expressed in the central nervous system, and their blockade by drugs such as thioperamide markedly enhances the activity of histaminergic neurons, as shown namely by the increases in histamine (HA) release and turnover in rodent brain (Arrang et al, 1987;Garbarg et al, 1989;Itoh et al, 1991;Mochizuki et al, 1991). The use of this prototypical autoreceptor antagonist in numerous studies to enhance brain HA release has been instrumental in establishing the roles of tuberomammillary neurons in behavior (for review, see Onodera et al, 1994;Hill et al, 1997;Brown et al, 2001).…”
mentioning
confidence: 99%